2005
DOI: 10.1186/1745-0179-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundAlthough the association between asthma and psychosocial factors has long been recognised, it is only in the last decade that the impact of coexisting asthma and depression has become the focus of considerable research interest. However, the findings so far have been confusing and often contradictory. This paper sets out a methodical review and appraisal of the literature to date, including suggestions for future research.MethodPubMed and PsycINFO databases were used to search for English-language ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(52 citation statements)
references
References 58 publications
0
51
0
1
Order By: Relevance
“…48 There is similar evidence for high psychological morbidity in asthma and CHD. 49,50 Poor health outcomes associated with psychological symptoms…”
Section: High Psychological Morbidity Associated With Long-term Condimentioning
confidence: 99%
See 3 more Smart Citations
“…48 There is similar evidence for high psychological morbidity in asthma and CHD. 49,50 Poor health outcomes associated with psychological symptoms…”
Section: High Psychological Morbidity Associated With Long-term Condimentioning
confidence: 99%
“…Depression has an adverse effect on QoL in asthma, 49 COPD, 51 diabetes 52 and CHD. 53 Depression has been linked to adverse morbidity and mortality in CHD 53,54 and COPD.…”
Section: High Psychological Morbidity Associated With Long-term Condimentioning
confidence: 99%
See 2 more Smart Citations
“…In this vein, researchers have found that in adults with asthma, the presence of depressive symptoms reduces the compliance and control of the treatment for the disease (Bosley, Fosbury, & Cochrane, 1995;Strine et al, 2008) and that children with asthma and a comorbid depressive disorder have increased healthcare utilization compared to children with asthma but without depressive disorder (Richardson et al, 2006). Additionally, researchers have found that depressive symptoms may influence the cognitive functioning of individuals with asthma (DiMatteo et al, 2000;Opolski & Wilson, 2005).…”
Section: Asthma and Depressionmentioning
confidence: 99%